Purine Metabolism in Acute Cerebral Ischemia - Ye. V. Oreshnikov; S. F. Oreshnikova; I. V. Madyanov (Общая реаниматология, 2008)
Objective: to study the specific features of purine metabolism in clinically significant acute cerebral ischemia. Subjects and materials. Three hundred and fifty patients with the acutest cerebral ischemic stroke were examined. The parameters of gas and electrolyte composition, acid-base balance, the levels of malonic dialdehyde, adenine, guanine, hypox-anthine, xanthine, and uric acid, and the activity of xanthine oxidase were determined in arterial and venous bloods and spinal fluid. Results. In ischemic stroke, hyperuricemia reflects the severity of cerebral metabolic disturbances, hemodynamic instability, hypercoagulation susceptiility, and the extent of neurological deficit. In ischemic stroke, hyperuri-corachia is accompanied by the higher spinal fluid levels of adenine, guanine, hypoxanthine, and xanthine and it is an indirect indicator of respiratory disorders of central genesis, systemic acidosis, hypercoagulation susceptibility, free radical oxidation activation, the intensity of a stressor response to cerebral ischemia, cerebral metabolic disturbances, the depth of reduced consciousness, and the severity of neurological deficit. Conclusion. The high venous blood activity of xanthine oxidase in ischemic stroke is associated with the better neurological parameters in all follow-up periods, the better early functional outcome, and lower mortality rates. Key words: hyperuricemia, stroke, xanthine oxidase, uric acid, cerebral ischemia.